Intestinal Behcet’s syndrome with an unusual complication bladder-intestines fistula and urinary tract infections—A case report - Deng, Jiewen; Fan, Xuanming; Guo, Hui; Gao, Jie; Li, Xuan; Wan, Wei (Frontiers in Cellular and Infection Microbiology, 2023)
A 33-year-old male patient with Behcet's syndrome for 17 years appeared with abdominal pain and fever. The abdominal CT was suggestive of an acute ileocecal intestinal perforation. And the symptoms disappeared after conservative treatment. Some related examinations, particularly capsule endoscopy added, were performed to explain the phenomenon of food residue in the urine after admission. These results indicated that intestine-urinary tract fistula formation was the outcome of intestinal Behcet's syndrome perforation. This is a very rare case of intestinal Behcet's syndrome complicated by entero-urinary fistula formation and urinary tract infections with abdominal symptoms as the main manifestation. We report this history to emphasize that in addition to surgical methods of diagnosis and treatment for intestinal Behcet’s disease at the acute stage, the capsule endoscopy is conducive to the assessment of the disease and treatment of the original disease.